2007
DOI: 10.1111/j.1532-849x.2007.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Variations of L*a*b* Values among Vitapan® Classical Shade Guides

Abstract: The differences observed between shade guides are larger than the variations induced by the experimental method. The difference in E values for the shades C1 and C2 is 2.19; hence the observed E(r) of 3.05 between shade tabs of the same shade (C1) is larger than the changes in color between shades. This large a variation in what are claimed as identical shade tabs is deemed of clinical importance, and therefore, the shade guides should not be considered interchangeable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 7 publications
0
47
0
1
Order By: Relevance
“…The use of such softwares on PCs has Fig. 3 a-b L* versus C*ab for representative A1, A2, A3 and A3,5 shade tabs obtained at a 2,700 K and 2700-6500 K colour temperature using the digital imaging method b 6,500 K colour temperature using the digital imaging method and the colorimeter controversial outcome [18][19][20]. In those studies, the studied material was the tooth brightness and translucency after vital bleaching using L* and RGB values.…”
Section: Discussionmentioning
confidence: 99%
“…The use of such softwares on PCs has Fig. 3 a-b L* versus C*ab for representative A1, A2, A3 and A3,5 shade tabs obtained at a 2,700 K and 2700-6500 K colour temperature using the digital imaging method b 6,500 K colour temperature using the digital imaging method and the colorimeter controversial outcome [18][19][20]. In those studies, the studied material was the tooth brightness and translucency after vital bleaching using L* and RGB values.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yilmaz et al reported that the replication of high-value shades was observed to be reliable [9], and Lagouvardos et al indicated that some shades produced a more reliable and valid match than others regardless of the brightness [14]. Other factors such as the region of the crown [15][16][17] and the type of shade guide used to select the color in the dental office and in the dental laboratory [2,13,14,[18][19][20] have also been reported to be related.…”
Section: Introductionmentioning
confidence: 99%
“…(6)(7)(8)(9) There have also been reported discrepancies related within similar shade tab from the same manufacturer, and also between different shade guide systems. (10)(11) Therefore, absolute care must be followed in performing shade matching including handling and sterilization of the shade guide itself. Manufacturer's recommendation for sterilization of conventional shade guide includes chemical disinfectants with solutions that doesn't include component of phenol or methyl ethyl ketone.…”
Section: Introductionmentioning
confidence: 99%